Analysis of mortality and cost implications in aspiration pneumonia: A retrospective study - Bektaş Aksoy, Hayriye; Günaydın, Selda; Aksoy, İskender (The European Research Journal, 2025)
Objectives: The purpose of this study is to analyze the demographic factors, clinical outcomes, and healthcare costs associated with aspiration pneumonia, focusing on mortality rates and the economic burden on healthcare systems. Methods: A retrospective observational study was conducted using data from patients admitted to the Emergency Department of Samsun Training and Research Hospital between January 2016 and December 2017 and followed in the intensive care unit with a diagnosis of aspiration pneumonia. The study recorded demographic-clinical parameters, nutritional methods, intensive care unit (ICU) length of stay, clinical outcomes, and cost situations for 60 patients. Results: The average age of male patients was found to be higher than that of female patients, with a broader age range observed among men. The study identified significantly higher ICU stays and costs for deceased patients. The age group with the highest mortality rate was 66-80 years. Additionally, advanced nutritional support methods, such as enteral and parenteral nutrition, were associated with higher mortality rates. Conclusions: Aspiration pneumonia represents a significant economic burden on healthcare systems, particularly for patients with poor outcomes. Age, ICU length of stay, and the need for advanced nutritional support are key factors influencing mortality. The findings underscore the need for multidisciplinary care approaches and early identification of high-risk patients to optimize treatment and resource allocation.